An Investigation into the Physical Mechanisms of Leak Noise Propagation in Buried Plastic Water Pipes: A Wave Dynamic Stiffness Approach - Scussel, Oscar; Brennan, Michael J. [UNESP]; Muggleton, Jennifer M.; de Almeida, Fabrício C. L. [UNESP]; Joseph, Phillip F.; Gao, Yan (MDPI, 2024)
In buried plastic water pipes, the predominantly fluid-borne wave is of particular interest, as it plays a key role in the propagation of leak noise. Consequently, it has been studied by several researchers to determine the speed of wave propagation and its attenuation with distance. These features are encapsulated in the wavenumber. By examining the factors that govern the behaviour of this wavenumber, this paper presents an in-depth examination of the physical mechanisms of leak noise propagation. To achieve this, an alternative physics-based model for the wavenumber is developed, using the concept of the wave dynamic stiffnesses of the individual components within the pipe system, i.e., the water in the pipe, the pipe wall, and the surrounding medium. This facilitates a clear interpretation of the wave behaviour in terms of the physical properties of the system, especially the interface between the pipe and the surrounding medium, which can have a profound influence on the leakage of acoustic energy from the pipe wall into the external medium. Three systems with different types of surrounding medium are studied, and the factors that govern leak noise propagation in each case are identified. Experimental results on two distinct test sites from different parts of the world are provided to validate the approach using leak noise as an excitation mechanism.
Keywords: buried plastic water pipes; leak noise wave propagation; predominantly fluid-borne wavenumber; wave dynamic stiffness